Relative biocompatibility of micro-hybrid and nano-hybrid light-activated composite resins - Abiodun Olabisi Arigbede; Bukola Folasade Adeyemi; Omowumi Femi-Akinlosotu (Tabriz University of Medical Sciences, 2017)
Background. In vitro studies have revealed a direct association between resin content and cytotoxicity of composite re-sins; however, implantation studies in this regard are sparse. This study investigates the relationship between filler content of composite resins and biocompatibility. Methods. This research employed twelve 180‒200-gr male Wistar rats, 1 nano-hybrid (Prime-Dent Inc.) and 1 micro-hybrid (Medental Inc.) composite resins containing 74% and 80‒90% filler content, respectively. The samples were assessed on the 2nd, 14th and 90th day of implantation. Four rats were allocated to each day in this experimental study. A section of 1.5mm long cured nano-hybrid and micro-hybrid materials were implanted into the right and left upper and lower limbs of the rats, respectively. Eight samples were generated on each day of observation. Inflammation was graded according to the criteria suggested by Orstavik and Major. Pearson's chi-squared test was employed to determine the relationship between the tissue responses of the two materials. Statistical significance was set at P < 0.05. Results. The average grade of inflammation for the nano-hybrid on the 2nd day of implantation was 3.3. The micro-hybrid resin had a score of 3.0 for cellular inflammation. On the 14th day, the micro-hybrid resin also exhibited a lower average grade for cellular inflammation. On the 90th day, the micro-hybrid resin had a higher grade of inflammation (0.9) compared to 0.3 recorded for nano-hybrid. The composite resins with higher filler content elicited a significantly lower grade of inflammation irrespective of the duration (χ=20.000, df=8, P=0.010) while the composite resins with lower filler content elicited a significantly lower inflammatory response on the 90th day (χ=4.000, df=1, P=0.046). Conclusion. The composite resins with higher filler content generally elicited significantly lower grades of inflammation, and the composite resins with lower filler content exhibited significantly lower inflammatory response on the 90th day of implantation.